The Prophylactic Anti-Inflammatory Effect of Omega-7 Against Paracetamol-Induced Liver Injury in Rats - Hameed, Hadeel A; Hassan, Ali F (The Iraqi Journal of Veterinary Medicine, 2022)
Paracetamol poisoning, whether intentionally or accidentally, is one of the main public health problems since the prevalence of its toxicity increased significantly in many countries. Currently, paracetamol is one of the primary causes of acute liver failure worldwide. The aim of this study was to investigate the potential prophylactic effect of omega-7 fatty acid in protecting male rats’ livers from paracetamol-induced liver damage. Thirty albino male rats were divided randomly and equally into five groups and then treated as follows: Group 1 (negative control) rats were orally given liquid paraffin for seven consecutive days. Group 2 (positive control) rats were orally given liquid paraffin for seven consecutive days and a single injection of paracetamol (500 mg/kg) intraperitoneally on day eight of the experiment. Group 3 rats were orally given omega-7 (300 mg/kg) for seven consecutive days. Group 4 rats were orally given a single dose of omega-7 (100 mg/kg/day) for 7 days and a single injection of paracetamol (500 mg/kg) intraperitoneally on day eight of the experiment. Group 5 rats were orally given a single dose of omega-7 (300 mg/kg/day) for 7 days and a single injection of paracetamol (500 mg/kg) intraperitoneally on day eight of the experiment. After 24 h of the endpoint of treatment (on day 9), blood samples were collected, and serum was prepared for the evaluation of tumor necrosis factor-alpha (TNF-α) and interleukin-10 (IL-10). This study found that rats given paracetamol had a significant (P<0.05) increase in serum levels of TNF-α and IL-10, whereas rats previously given oral administration of omega-7 fatty acid before injection of paracetamol resulted in a significant decrease (P<0.05) of these cytokines. Oral omega-7 fatty acid supplementation may help to prevent liver damage caused by paracetamol.